The Significance of Compliance Functions in Ensuring the Continuity of Sharia Insurance Companies - Deny Susanto (Journal of Nusantara Economy, 2023)
This paper examines the crucial importance of compliance duties in safeguarding the viability of Sharia insurance companies. Sharia insurance possesses distinct attributes that necessitate strict compliance with the tenets of Islamic law. Compliance is an essential factor in ensuring that Sharia insurance businesses adhere to the ethical norms and sharia principles that form the basis of their operations. The talk commenced by examining the legal framework governing Sharia insurance and identifying crucial elements necessitating adherence. The focus was on the principles of transparency, justice, and the prohibition of interest in Sharia insurance policies. Compliance functions serve as a mechanism to guarantee that organizations adhere to relevant legislation and standards, thereby reducing the likelihood of violations and safeguarding the interests of law enforcement and other stakeholders. This article examines the favorable influence of compliance functions on corporate reputation, market competitiveness, and consumer confidence. The viability of Sharia insurance firms is contingent upon their ethical conduct and adherence to Sharia rules in their operations. Compliance serves as both an internal monitoring mechanism and a strategic ally in fostering long-term sustainability. Based on an examination of existing literature, case studies, and thorough research, this essay asserts that ensuring compliance and functional integrity is crucial for establishing a strong basis for Sharia insurance firms. Hence, a comprehensive comprehension of Sharia law, rules, and optimal methodologies within the realm of Sharia insurance becomes imperative for professionals, governing bodies, and scholars involved in this domain. Efficient execution of the compliance function will bolster long-term expansion, durability, and public trust in the Shariah insurance sector.